Issues of Implementing Foreign Experiences in the Music Education Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the importance and challenges of implementing foreign experiences in the music education process. It highlights how educational practices from other countries can enhance the quality of music education and contribute to the development of students' musical skills, creativity, and cultural understanding. The study explores various international models of music education, comparing their methods with local practices to identify areas for improvement. Data were collected through surveys, interviews with educators, and case studies of music education systems from countries known for their strong music education programs. The results reveal that integrating foreign practices can offer valuable insights into curriculum development, teaching methods, and student engagement. The study concludes by proposing recommendations for incorporating successful foreign practices into local music education systems to improve overall outcomes.